(untitled) (LINGUISTICA, 2015)
This study deals with feminism Spirit™s reflections on ˜Jordan O™Neil™ in G.I Jane movie. The study is conducted by using descriptive qualitative approach. The objectives of the study are to find out kinds of oppression faced by O™Neil and her feminism spirit™s reflections in term of oppression that she had faced. The data are collected from dialogues and scenes in the movie. The object of the study is Jordan O™Neil as the female main character. The study revealed that there are three major oppressions faced by O™Neil according to Young™s theory: being marginalized,exploited and experiencing powerlessness. Feminism Spirit™s reflections on Jordan O™Neil in term of oppression that she had already faced are three major parts: being persistent, independent, and courageous.